Effects of Different Hangboard Training Intensities on Finger Grip Strength, Stamina, and Endurance - Devise, Marine; Lechaptois, Clément; Berton, Eric; Vigouroux, Laurent (Frontiers in Sports and Active Living, 2022)
Climbing-specific training programs on hangboards are often based on dead-hang repetitions, but little is known about the real intensity applied during such effort. The aim of this study was to quantify and compare the effects of different training intensities (maximal, high submaximal, and low submaximal intensities) on the fingers' physiological capabilities using a hangboard fitted with force sensors. In total, 54 experienced climbers (13 women and 41 men) were randomly divided into four groups, with each group following different training intensity programs: maximal strength program performed at 100% of the maximal finger strength (MFS; F100), intermittent repetitions at 80% MFS (F80), intermittent repetitions at 60% MFS (F60), and no specific training (control group). Participants trained on a 12 mm-deep hold, twice a week for 4 weeks. The MFS, stamina, and endurance levels were evaluated using force data before and after training. Results showed similar values in the control group between pre- and post-tests. A significantly improved MFS was observed in the F100 and F80 groups but not in the F60 group. Significantly higher stamina and endurance measurements were observed in the F80 and F60 groups but not in the F100 group. These results showed that a 4-week hangboard training enabled increasing MFS, stamina and endurance, and that different improvements occurred according to the level of training intensity. Interestingly, the different intensities allow improvements in the targeted capacity (e.g., stamina for the F80 group) but also in the adjacent physiological capabilities (e.g., MFS for the F80 group).